Fostering possibility within vulnerability: Rohingya’s endeavour for adaptation in Nepal - Rai, Prawesh (Nepal Sociological Journal, 2025)
Although the impact of the Rohingya refugee influx in Nepal is relatively minor compared to other host countries, a notable number of Rohingya have been unofficially residing in Nepal for over a decade. In the absence of formally arranged refugee camps or resettlement programs, they live in self-managed settlements under an unsorted legal status. This paper explores the decade- long journey of Rohingya adaptation in Nepal, tracing three major phases of transition in their efforts to integrate and sustain themselves. The findings reveal that, over time, the Rohingya commune has fostered a remarkable sense of collective agency in responding to contingencies with innovativeness and resilience. Thus, they have gradually moved from a condition of mere survival to one of basic sustenance. This paper, rather than portraying the Rohingya just as passive victims of structural constraints, highlights their resilience, collective agency, and adaptability.